ALKITAB DI DUNIA POSTMODERN - Yunus Selan (STT Pelita Dunia, 2019)
Abstract: This article talks about the Bible in the Postmodern world. Hopefully this writing or research can help to understand postmodern people assessing and using the Bible. Abstract: This article talks about the Bible in the Postmodern world. Hopefully this writing or research can help to understand postmodern people assessing and using the Bible. Abstraksi: Artikel ini berbicara tentang Alkitab di dunia Postmodern. Kiranya tulisan atau penelitian ini dapat menolong untuk memahami orang-orang postmodern menilai dan menggunakan Alkitab.